Pregnancy-induced hypertension-related chorioretinitis resembling uveal effusion syndrome: A case report. Issue 30 (July 2018) - Sato, Tomohito; Takeuchi, Masaru
Abstract: Rationale: Pregnancy-induced hypertension (PIH) is a major cause of maternal and fetal mortality. Hypertensive choroidopathy is a preliminary sign of vasogenic edema in the choroid, and is associated with PIH. Here, we report a post-natal case of PIH-related chorioretinitis with bilateral severe serous retinal detachment (SRD) resembling uveal effusion syndrome. Patient concerns: A 35-year-old woman was diagnosed with severe PIH at 37 weeks of pregnancy. She underwent an emergency cesarean delivery. Four days after delivery, she perceived a sudden decrease of vision. At presentation, fundus examination demonstrated bullous SRD and multiple white mottles in the posterior poles of both eyes. Optical coherence tomography (OCT) showed macula edema and retinal pigment epithelium (RPE) folds. Indocyanine green angiography (ICGA) demonstrated delayed filling of choroidal circulation in the early phase and multiple hyperfluorescent spots in the mid phase. Diagnoses: PIH. Interventions: Antihypertension treatment alone resulted in gradual resolution of the SRD. Outcomes: At 463 days after delivery, fundus photographs of both eyes showed leopard spots corresponding to hyperautofluorescent spots with dark rim observed on fundus autofluorescence images. Lessons: Ophthalmologists should be aware of PIH-related chorioretinitis with similar clinical manifestations as uveal effusion syndrome, and should treat with antihypertensive agents in cooperation with obstetricians.